2020
DOI: 10.1002/phar.2364
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Patient Outcomes with PD‐1/PD‐L1 Immune Checkpoint Inhibitors for the First‐Line Treatment of Advanced Non–Small Cell Lung Cancer

Abstract: The rapidly expanding repertoire of immune checkpoint inhibitors (ICIs) now includes two agents, pembrolizumab and atezolizumab, approved for first‐line treatment of advanced non–small cell lung cancer (aNSCLC) as monotherapy or as part of chemoimmunotherapy. This review summarizes the clinical evidence supporting these indications, with a focus on strategies to optimize patient outcomes. These strategies include patient and tumor factors, adverse‐effect profiles, pharmacokinetic and pharmacodynamic drug inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…For their nature, ICIs restore the cellular-mediated immunocompetence. By blocking the checkpoints PD-1/PD-L1 and CTLA4/B7, the cellular mediated anti-tumor activity of the immune system is then successfully restored and the cancer cells can be efficiently eliminated by the immune system [ 58 ].…”
Section: Covid-19 and Anti-cancer Therapy: Advantages And Disadvanmentioning
confidence: 99%
“…For their nature, ICIs restore the cellular-mediated immunocompetence. By blocking the checkpoints PD-1/PD-L1 and CTLA4/B7, the cellular mediated anti-tumor activity of the immune system is then successfully restored and the cancer cells can be efficiently eliminated by the immune system [ 58 ].…”
Section: Covid-19 and Anti-cancer Therapy: Advantages And Disadvanmentioning
confidence: 99%
“…They include an anti-PD-1, anti-PD-L1 and anti-CTLA-4 antibody which shows a progressive immunotherapy treatment of solid tumors includes the head and neck, urothelial, melanoma, haematological, renal carcinoma and lung cancer, it could be alone, in combination or with chemotherapy [ 60 , 61 , 62 ]. The anti-tumor cellular mediated immune response is recovered, and the cancer cells could be removed from the immune system by the blockage of PD-1/PD-L1 and CTLA4/B7 checkpoints ( Figure 6 ) [ 63 ].…”
Section: How Can Blockage By Immune Checkpoint Inhibitors Be Beneficial For the Cancer Patients?mentioning
confidence: 99%
“…In sharp contrast to the way that chemotherapy and radiotherapy exert their therapeutic effect, ICIs favor immunocompetence [ 57 ]. It has been suggested that the ability of ICIs to enhance the effector function of cytotoxic T-cells may explain the shorter recovery period from COVID-19 in patients with cancer receiving immunotherapy [ 52 ].…”
Section: Covid-19mentioning
confidence: 99%